Effect of composite technologies on the mechanical properties and biodegradability of agricultural polymeric materials - Md Sam, Nor Syahidah; Krishnen, Ganisan; Baharulrazi, Norfhairna; Abdullah, Luqman Chuah; Abdul Majid, Rohah (Universiti Putra Malaysia Press, 2025)
Polymeric materials are widely applied in agriculture for purposes such as weed control, nutrient delivery, and the controlled release of pesticides and herbicides. However, their environmental impact, particularly from synthetic polymers like polyethylene and polystyrene, stems from their resistance to degradation. With an estimated 80% of global plastic waste accumulating in ecosystems or landfills, the development of biodegradable alternatives has become a critical concern. This has led to a growing demand for biodegradable polymers in applications such as plastic mulching and controlled-release systems, aiming to reduce pollution, support soil health and ease post-harvest residue management. This paper provides an overview of recent developments in biodegradable polymer composites, with a focus on how composite technologies enhance both the mechanical performance and biodegradability of these materials. It also provides an overview of the growing recognition of polymer composites for their role in improving the efficiency and precision of nutrient, pesticide, and herbicide delivery to plants, minimizing environmental losses and enhancing resource use. The discussion emphasizes the need for biodegradable polymers to meet functional criteria similar to synthetic plastics, such as adequate tensile strength and elongation while remaining capable of degrading under agricultural conditions. The integration of fillers, reinforcements, and polymer blends has shown promise in improving durability during use and facilitating breakdown afterward. Such dual performance is vital for sustainable agricultural systems. This review aims to offer insights into the role of composite technologies in advancing biodegradable polymer materials for agriculture, supporting both efficient input delivery and long-term environmental compatibility.